Sistem Pakar Menggunakan Metode Bayes untuk Analisis Penyakit Mulut pada Kucing - Fahrul Razi (Jurnal Sistim Informasi dan Teknologi, 2022)
The expert system using the Bayes method results in an analysis of oral diseases in cats. This expert system can be used by the general public to detect oral diseases in cats without having to come directly to the vet. Building an expert system software using the Bayes method to diagnose oral disease in cats equipped with solutions according to the indicated disease. The data that is processed in the expert system for detecting oral disease in cats is obtained from the results of interviews with animal disease specialists. The dataset used consists of 8 diseases. This expert system was built using the Bayes method. This expert system is made using a rule-based application and uses the PHP and MySQL programming languages. The results of testing this method are the types of diseases according to the symptoms entered by the user and solutions for disease prevention indicated by the system. This expert system is useful for the community to find out oral diseases in cats without having to come directly to a veterinarian. And can help doctors work in improving the accuracy of oral disease analysis in cats.